2002
DOI: 10.2169/internalmedicine.41.34
|View full text |Cite
|
Sign up to set email alerts
|

Adult T-cell Leukemia (ATL) Cells which Express Neural Cell Adhesion Molecule (NCAM) and Infiltrate into the Central Nervous System.

Abstract: Weencountered a patient with adult T-cell leukemia/lymphoma (ATL) which expressed neural cell adhesion molecule (NCAM). The tumor cells markedly infiltrated the central nervous system (CNS) during the course of the ATL. The patient died 20 months after disease onset, which was considered to be early in the course. During the invasion of the CNS, the surface phenotype of the peripheral blood ATL cells by flow cytometric analysis was CD2+, CD3+, CD4+, CD7-, CD8-, CD16-, NCAM(CD56)+, HLA-DR-. We speculate that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…It rarely presented as an isolated event (8.3%) or even as the initial site of involvement (29.2%) in our series. [18][19][20][21][22][23][24][25][26][27][28] In summary, ATLL is a rare mature T-cell lymphoma, especially in nonendemic regions such as the Central-Midwestern region of the United States, and carries an aggressive clinical course. CNS involvement also occurred with relapsed disease and with extensive systemic disease in the majority of cases in this series, whereas primary CNS disease was rare.…”
Section: Discussionmentioning
confidence: 99%
“…It rarely presented as an isolated event (8.3%) or even as the initial site of involvement (29.2%) in our series. [18][19][20][21][22][23][24][25][26][27][28] In summary, ATLL is a rare mature T-cell lymphoma, especially in nonendemic regions such as the Central-Midwestern region of the United States, and carries an aggressive clinical course. CNS involvement also occurred with relapsed disease and with extensive systemic disease in the majority of cases in this series, whereas primary CNS disease was rare.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that this manifestation was in fact a result of biological properties of leukemic cells regardless of the type and immune leukocytes. These properties were being translated by the aberrant expression of adhesion molecules such as CD44 and the integrin family of molecules such as VLA-4 and LFA-1 (27)(28)(29)(30)(31)(32).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the expression of CD56, a neural celladhesion molecule (NCAM), was elevated in adult ALL samples with CNS involvement (Ravandi et al, 2002;Hu et al, 2017). NCAM was also associated with intracerebral and leptomeningeal infiltration in adult T cell leukemia (ATL) (Hashiguchi et al, 2002). Thus, NCAM was proposed as a marker for CNS infiltration and poor prognosis in ALL, and ATL.…”
Section: Cell Adhesion In Leukemic Cell Colonization Of the Central Nervous Systemmentioning
confidence: 99%